The princess of Las Vegas : a novel - Bohjalian, Chris, 1962- (Doubleday, 2024)
"The book revolves around Crissy, the star of a beloved Princess Diana tribute show in Las Vegas, and her estranged sister Betsy, a therapist who works with children and adolescents in Vermont. Betsy's boyfriend Frankie works in a mysterious branch of cryptocurrency and, seemingly out of nowhere, proposes that they move to Las Vegas together. Betsy and Crissy must navigate how to go about their newfound physical proximity to one another and their respective relationships with Betsy's foster child Marisa, who moves with Betsy and Frankie to Vegas. When Crissy meets a handsome, secretive Russian man named Yevgeny, Crissy and Betsy soon find themselves in a dangerous web of greed, crypto-mafia schemes, and murder"--